1977
DOI: 10.1139/v77-564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an external electric field on the yield of trapped electrons in a γ-irradiated hydrocarbon glass

Abstract: NORIYUKI KATO, TOYOAKI KIMURA, and KENJI FUEKI. Can. J. Chem. 55,3973 (1977). Trapped electron yields were measured by means of optical absorption spectroscopy for a hydrocarbon glass y-irradiated at 77 K in the presence of an external electric field. It was observed that the yield of trapped electrons increased in .the presence of an external electric field as compared with that in the absence of an external electric field. The experimental results were analyzed theoretically and interpreted as due to overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Three main processes which are perturbed by the applied electric field are probably as follows: (1) the recombination process in which the recombination time, consequently the escape probability, depends upon the strength of the electric field and the angle between the direction joining the electron to the positive ion and that of the field; (2) the nonradiative transition process for electrons from a delocalized state to a localized state where the transition is a consequence of an electron-phonon coupling interaction; and (3) a transfer or detrapping process from a localized state to a delocalized state or another localized state by hopping or tunneling. 11 Kato et al 8 showed that the increase in the yield of e80f, e.g., ODe/ODq 1.06 for E = 50 kV cm-1, can be theoretically predicted by assuming that the electric field mainly perturbs process 1. They also comment that whatever the forms of the initial distribution function of thermalized electrons are, the calculated yield of eaof is always larger in the presence of an electric field than in ©…”
Section: Resultsmentioning
confidence: 99%
“…Three main processes which are perturbed by the applied electric field are probably as follows: (1) the recombination process in which the recombination time, consequently the escape probability, depends upon the strength of the electric field and the angle between the direction joining the electron to the positive ion and that of the field; (2) the nonradiative transition process for electrons from a delocalized state to a localized state where the transition is a consequence of an electron-phonon coupling interaction; and (3) a transfer or detrapping process from a localized state to a delocalized state or another localized state by hopping or tunneling. 11 Kato et al 8 showed that the increase in the yield of e80f, e.g., ODe/ODq 1.06 for E = 50 kV cm-1, can be theoretically predicted by assuming that the electric field mainly perturbs process 1. They also comment that whatever the forms of the initial distribution function of thermalized electrons are, the calculated yield of eaof is always larger in the presence of an electric field than in ©…”
Section: Resultsmentioning
confidence: 99%